Relevance of activated hepatic stellate cells in predicting the development of pediatric liver allograft fibrosis. Issue 6 (June 2016) - Venturi, Carla; Reding, Raymond; Quinones, Jorge Abarca; Sokal, Etienne; Rahier, Jacques; Bueno, Javier; Sempoux, Christine
Abstract : Activated hepatic stellate cells (HSCs) are the main collagen‐producing cells in liver fibrogenesis. With the purpose of analyzing their presence and relevance in predicting liver allograft fibrosis development, 162 liver biopsies of 54 pediatric liver transplantation (LT) recipients were assessed at 6 months, 3 years, and 7 years after LT. The proportion of activated HSCs, identified by α‐smooth muscle actin (ASMA) immunostaining, and the amount of fibrosis, identified by picrosirius red (PSR%) staining, were determined by computer‐based morphometric analysis. Fibrosis was also staged by using the semiquantitative liver allograft fibrosis score (LAFSc), specifically designed to score fibrosis in the pediatric LT population. Liver allograft fibrosis displayed progression over time by PSR% ( P < 0.001) and by LAFSc ( P < 0.001). The ASMA expression decreased in the long term, with inverse evolution with respect to fibrosis ( P < 0.01). Patients with ASMA‐positive HSCs area ≥ 8% at 6 months (n = 20) developed a higher fibrosis proportion compared to those with ASMA‐positive HSCs area ≤ 8% (n = 34) at the same period of time and in the long term ( P = 0.03 and P < 0.01, respectively), but not at 3 years ( P = 0.8). ASMA expression ≥ 8% at 6 months was found to be an independent risk factor for 7‐year fibrosis development by PSR% ( r 2 = 0.5; P < 0.01) and by LAFSc ( r 2 = 0.3; P = 0.03). Furthermore, ASMA expression ≥ 8% at 3 years showed an association with the development of fibrosis at 7 years ( P = 0.02). In conclusion, there is a high proportion of activated HSCs in pediatric LT recipients. ASMA ≥ 8% at 6 months seems to be a risk factor for early and longterm fibrosis development. In addition, activated HSCs showed inverse evolution with respect to fibrosis in the long term. Liver Transplantation 22 822–829 2016 AASLD .